Effect of the implementation of the high information guide in compliance puerperal care indications and newborn care mediate postpartum women served in the service of adolescent mother in the Maternal Perinatal National Institute-2012 - admin, admin (2018)
Objectives. To determine the effect of the implementation of the information brochure on compliance with the directions of postnatal care and newborn mediate the postpartum adolescents seen in adolescence Service National Perinatal Maternal Institute, 2012. Materials and methods. A quasi-experimental, prospective, counted with an experimental group and a comparison group. 120 postpartum women were evaluated at 60 postpartum adolescents in each group, divided into two groups: Group A patients was applied to an information and group B patients which were not subject to the information package, all served in the INMP from October 2011 to February 2012. Was estimated for qualitative variables, absolute and relative frequencies. In the case of quantitative variables were estimated as measures of central tendency mean, median, and measures of dispersion such as standard deviation and range. For the inferential analysis used the Student t test for independent samples and chi-square test of independence. Results. Most patients came from the districts of SJL 31,7%, 11,7% and SJM Villa el Salvador 10%, mean age 16,72 ± 1.3 years, 80% had secondary education, 70% were cohabiting. The 63,3% of deliveries were vaginal and 36.7% by caesarean average hospital stay was 3,43 ± 1,5 days. In the group that was applied orientation guide reached 63,3% compliance rated “Very Good”, compared with 6,7% in the group that did not undergo orientation guide. The level of compliance on newborn care was achieved 66,7% compliance rated “Very Good” compared with 16,7% in the control group, showing that there is a positive effect of the implementation of the informative guide High in compliance with the indications and postnatal care, finding relationship between the two variables (p <0,001). There is also a positive effect of the implementation of high-informative guide in meeting the indications and newborn care, relating both variables (p <0,001). Conclusions. The level of compliance orientation guide postpartum care and newborn reached significant positive effect.